‘Another Woman’ by Imptiyaz Dharker, and ‘I am Not That Woman’ by Kishwar Naheed: Marginalization, Resistance and Subversion - Khoche, Pranav (Integrated Journal for Research in Arts and Humanities, 2024)
The present paper attempts to analyse the theme of marginalization, subjugation and resistance in the selected poems, namely, ‘Another Woman' by Imptiyaz Dharker, and ‘I am Not That Woman’ by Kishwar Naheed and the paper also tries to show how the two poems can be linked as a sequel. While ‘Another Woman' depicts the mute acceptance of violence by a woman typically from the Indian subcontinent, the speaker in‘I am not that Woman' exhibits remarkable resistance to the tendency to stereotype women in the market economy as well as to the oppression in the guise of customs of patriarchal society. Though the overall background of the paper is feminist criticism, the aspects of marginalization, and resistance and subversion as a response are dealt with in detail in this paper.